PENGARUH FINANCIAL KNOWLEDGE TERHADAP KINERJA USAHA YANG DIMEDIASI OLEH VARIABEL FINANCIAL CONFIDENCE, FINANCIAL SELF – EFFICACY, FINANCIAL ATTITUDE, DAN FINANCIAL BEHAVIOUR: (Studi Pada Pelaku Usaha Bisnis Online Bidang Kuliner di Kota Malang) - ZA, Zahroh (Jurnal Administrasi Publik, 2024)
The Effect of Financial Knowledge on Business Performance as Mediated by the Variables Financial Confidence, Financial Self Efficacy, Financial Attitude and  Fianncial Behavior. The Covid-19 pandemic that occurred in early 2020 had a negative impact on the business world, including the culinary business. Financial-related abilities are very necessary in an effective recovery strategy in the areas of knowledge, confidence, self-efficacy, attitude and behavior. The aim of this research is to analyze the influence of financial knowledge on business performance through several mediating variables, namely financial confidence, financial self- efficacy, financial attitude, and financial behavior among online business actors in the culinary sector in Malang City. This research methodology uses Partial Least Squares (PLS) analysis as a testing tool with WarpPLS statistical assets. The results of this study show that financial knowledge has a significant effect on financial confidence, financial self-efficacy and financial attitude, while financial confidence and financial attitude have a significant effect on financial behavior, but financial self-efficacy has no significant effect on financial behavior. Furthermore, financial knowledge and financial behavior influence business performance.